Strategi Peningkatan Kemampuan Anak Usia Dini dalam Mengenal Warna melalui Metode Eksperimen - Nur Fikriyatul Khasanah; Nur Hani’ah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2018)
Early childhood is the most appropriate time to develop all its potential. One of the potentials that needs to be developed early on in children is the insight and sense of art in children. Art is one of the basic potentials of children and also one form of plural intelligence. So, developing children's artistic potential means developing their intelligence. This study aims to improve the ability of early childhood to recognize secondary colors through experimental methods. With the experimental method of direct involvement of children so that children gain direct experience in the learning process. This type of research is a collaborative classroom action research. Collaborative classroom action research ie researchers work closely with class teachers in conducting research. The results showed that the ability to recognize secondary colors can be improved by the experimental method. The learning process of children is given the opportunity to conduct experiments on colors that are simple and attractive to children. The results of the study increased gradually, which can be seen from the observational data on pre-action, Cycle I and Cycle II. The average percentage acquisition in pre-action was 44.89%, increased in Cycle I with a percentage of 60.67% and increased to 83.53% in Cycle II.